2005
DOI: 10.1115/1.2162905
|View full text |Cite
|
Sign up to set email alerts
|

An Analytical Model for the Prediction of Minimum Chip Thickness in Micromachining

Abstract: In micromachining, the uncut chip thickness is comparable or even less than the tool edge radius and as a result a chip will not be generated if the uncut chip thickness is less than a critical value, viz., the minimum chip thickness. The minimum chip thickness effect significantly affects machining process performance in terms of cutting forces, tool wear, surface integrity, process stability, etc. In this paper, an analytical model has been developed to predict the minimum chip thickness values, which are cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
140
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(147 citation statements)
references
References 11 publications
4
140
0
3
Order By: Relevance
“…When feed per tooth is 0.7 μm, the cutting forces nearby have obvious trends of first increasing and then decreasing, so the minimum chip thickness is approximate f z = 0.7 μm during micro-milling Inconel 718. The cutting edge radius of the adopted cutter is approximate R = 2 μm, so f z / R ≈ 0.35, which consistent with the conclusion that the minimum chip thickness to tool edge radius ratio is approximate 0.2~0.4 (Liu et al, 2006). To reduce the cutting forces, it is advisable to avoid minimum chip thickness, so as to extend the tool life and to increase processing efficiency.…”
Section: Feed Per Tooth's Influence On Cutting Forcessupporting
confidence: 54%
“…When feed per tooth is 0.7 μm, the cutting forces nearby have obvious trends of first increasing and then decreasing, so the minimum chip thickness is approximate f z = 0.7 μm during micro-milling Inconel 718. The cutting edge radius of the adopted cutter is approximate R = 2 μm, so f z / R ≈ 0.35, which consistent with the conclusion that the minimum chip thickness to tool edge radius ratio is approximate 0.2~0.4 (Liu et al, 2006). To reduce the cutting forces, it is advisable to avoid minimum chip thickness, so as to extend the tool life and to increase processing efficiency.…”
Section: Feed Per Tooth's Influence On Cutting Forcessupporting
confidence: 54%
“…Changed surface appearances from clean cut to burnished have been reported [4,5]. Experimental and theoretical studies have indicated the critical value of a c /r e to be between 0.1 and 0.5, depending on material machined and cutting conditions [6,7]. But little has been reported on variation of surface roughness with a c /r e .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many slip-line field models have been specifically developed for the microscale [9][10][21][22][23][24][25][26][27][28][29] and all of them consider a rounded tool edge.…”
Section: State Of the Artmentioning
confidence: 99%
“…Waldorf et al [9][10], Liu et al [23][24][25], Karpat et al [26], Yoon et al [27] and Ozturk et al [29];…”
mentioning
confidence: 99%